2003
DOI: 10.1111/j.0042-9007.2003.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation technique and white cell content influence the detectable levels of growth factors in platelet concentrates

Abstract: Dissolving PC in Triton-X-100 releases maximum quantities of growth factors from platelets. The release of each growth factor by any sample preparation method should be investigated and interpreted separately. The preanalytical sample-preparation method, as well as the platelet and WBC content, influence the measurable levels of growth factors in PCs. The results implicate the need to correct, considerably upwards, previous estimations of the PDGF content of platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
140
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(154 citation statements)
references
References 44 publications
9
140
1
4
Order By: Relevance
“…Platelet-derived growth factor concentrations have also been investigated by several other laboratories (Christgau et al, 2006;Cognasse et al, 2006;Doucet et al, 2005;Frechette et al, 2005;Gruber et al, 2002;Kaps et al, 2002;lacoste et al, 2003;Ogino et al, 2006;Schallmoser et al, 2007;Shen et al, 2006;Weibrich et al, 2002;Zimmermann et al, 2003). the results of these analyses are not comparable with our results, because of different preparation methods: All except el Backly et al and Gruber et al (el Backly et al, 2011;Gruber et al, 2002) stored platelets in serum, which also contains growth factors, and/or in platelet additive solution.…”
Section: Stimulation Of Erk1/2 Map Kinasescontrasting
confidence: 69%
“…Platelet-derived growth factor concentrations have also been investigated by several other laboratories (Christgau et al, 2006;Cognasse et al, 2006;Doucet et al, 2005;Frechette et al, 2005;Gruber et al, 2002;Kaps et al, 2002;lacoste et al, 2003;Ogino et al, 2006;Schallmoser et al, 2007;Shen et al, 2006;Weibrich et al, 2002;Zimmermann et al, 2003). the results of these analyses are not comparable with our results, because of different preparation methods: All except el Backly et al and Gruber et al (el Backly et al, 2011;Gruber et al, 2002) stored platelets in serum, which also contains growth factors, and/or in platelet additive solution.…”
Section: Stimulation Of Erk1/2 Map Kinasescontrasting
confidence: 69%
“…The syringes were then frozen at −80°C and thawed at 37°C 3 times (Zimmermann et al, 2003) to allow the release of platelet-derived factors. The PC was subjected to bacteriological examination to verify its sterility.…”
Section: Preparation Of Platelet Concentratementioning
confidence: 99%
“…Nevertheless, it is doubtful that the clotting process releases all PLT-derived GFs into the serum. Recently we showed that PLT destruction by the detergent Triton X-100 causes the release of much more GFs from PLTs into the supernatant than do in vitro clotting processes (25 ). In addition, Tezono et al (26 ) recently demonstrated that VEGF is partially trapped within fibrin clots.…”
mentioning
confidence: 97%